Certain elements of population retaining ability and the ability to economically provide for a population of the countryside - Tikász, Ildikó Edit (Applied Studies in Agribusiness and Commerce, 2008)
According to the data of population density, most of Hungary’s territory has rural features. Achieving EU supports in order to focus on developing the most underdeveloped communities, and in order to lessen the differences between communities, to establish priorities and to determine the rank of rural communities based on their development potential is necessary.The need of measurability arises because of comparison and classification.A possible target area is an analysis of population retaining ability and the ability to economically provide for a population of rural areas.